Museu d'Art Espanyol Contemporani Fundación Juan March Palma de Mallorca. : Texte/Texts Juan Manuel Bonet - Javier Maderuelo. - Bonet, Juan Manuel; Maderuelo, Javier; Museu d'Art Espanyol Contemporani - Fundación Juan March, Palma de Mallorca (Madrid : Editorial de Arte y Ciencia, 1996)
This catalogue features commented reproductions of all the 57 pictures and sculptures exhibited in the Museu d'Art Espanyol Contemporani of the Fundación Juan March in Palma de Mallorca. It opens with a brief introduction to the museum and the different artistic tendencies and generations represented here. This is followed by notes on the life and career of each of 57 Spanish artists included in the collection, accompanied by a description of the works on display. The order in which the commentaries are presented offers the reader a concise vision of the evolution of the different artistic movements of the 20th century, from cubism to the present day. The texts have been written by the art historians and critics Juan Manuel Bonet and Javier Maderuelo.
Aguilar, Sergi ; Alfaro, Andreu ; Amat, Frederic ; Barcelo, Miquel ; Bordes, Juan ; Broto, José Manuel ; Campano, Miguel Angel ; Canelo, Luis ; Canogar, Rafael ; Chillida, Eduardo ; Chirino, Martin ; Clave, Antoni ; Cuixart, Modest ; Dali, Salvador ; Delgado, Gerardo ; Equipo Cronica ; Farreras, Francisco ; Feito, Luis ; García Sevilla, Ferran ; Genoves, Juan ; Gomez Perales, José Luis ; González, Julio ; Gordillo, Luis ; Grau, Xavier ; Gris, Juan ; Guerrero, José ; Guinovart, Josep ; Hernandez Pijuan, Juan ; Laffon, Carmen ; Lootz, Eva ; López Garcia, Antonio ; López Hernández, Julio ; Millarès, Manuel ; Miro, Joan ; Mompo, Manuel H. ; Munoz, Lucio ; Navarro Baldeweg, Juan ; Oteiza, Jorge ; Palazuelo, Pablo ; Picasso, Pablo ; Pérez Villalta, Guillermo ; Quintero, Daniel ; Rafols-Casamada, Albert ; Rivera, Manuel ; Rueda, Gerardo ; Saura, Antonio ; Sempere, Eusebio ; Serrano, Santiago ; Sevilla, Soledad ; Sicilia, José Maria ; Solano, Susana ; Teixidor, Jordi ; Torner, Gustavo ; Tàpies, Antoni ; Valdés, Manuel ; Villalba, Darío ; Zobel, Fernando
Duits & Engels
boek